TINJAUAN HUKUM INVESTASI WARGA NEGARA ASING DI INDONESIA BERDASARKAN PERJANJIAN AKTA OTENTIK - Yanis, Junilda (Journal of Law ( Jurnal Ilmu Hukum ), 2018)
ABSTRACTThe form of authentic deed is determined by law, while officials who can make it inevitable so that the same weight must also be determined by law or legislation. Making foreign investments in Indonesia, of course Indonesian citizens with foreign citizens or both companies in the form of limited liability companies (PT) must face the authorized official, namely a notary to make an authentic deed which contains the agreement agreed between the two parties. party.This study the author uses normative research methods, namely by library research. And in order to complete this study the author also conducted a little interview. The Law approach was carried out in this study, namely by examining all laws and regulations relating to research.The results of the research can be known as the main conditions in the process of establishing a Foreign Investment Limited Liability Company in Indonesia are the Identity of Parties as well as valid Foreign Citizen Passports, and later in the implementation of Investments by foreign nationals in Indonesia, with the presence of foreign Investors themselves to investing in Indonesia in this study can be through several ways of direct investment by establishing a new limited liability company or buying part or all of the shares in a limited liability company, which as stated in article 5 paragraph (2) of Law Number 25 of 2007 concerning Investment that planting compulsory foreign capital in the form of a limited liability company based on Indonesian law, in order to establish a limited liability company a foreign investor must face the Notary to make an authentic deed.Keywords: Notary, Investment, and Agreement.